İstanbul Sokakları: 101 Yazardan 100 Sokak - Dilek Germiyanoğlu (Türk Kütüphaneciliği)
The book, which is about the 100 streets of Istanbul as seen by 101 authors, was completed at the end of eight years. The 101 authors are made up of a group of 150 which constantly changed between the years 2002-2007. Out of the 101 authors, 25 are women; the oldest author was born in 1925; the youngest was born in 1983; 10 is not known as men of letters and 30 are known as poets. Out of the 100 streets, 35 are on the Anatolian side of Istanbul.